The Study of the Authenticity of Ketoprofen by the Thermodoserpion Surface Ionization Spectroscopy Method - Ahmadullo qizi, Guljahon Abdurahimova; Sodiqovich, Jalilov Fazliddin (Journal of Innovation in Education and Social Research, 2024)
This article provides information on medicinal properties of Ketoprofen, its use in medicine and pharmaceuticals, limits of action, chemical composition. An experiment to determine the authenticity of Ketoprofen is presented, the special apparatus and the conditions in it are explained in detail. In different countries of the world, information about the different use of this medicinal substance has been collected.